2015
DOI: 10.1039/c5cp00663e
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating interfacial hydrogens at palladium via STM

Abstract: In this contribution, we provide a detailed dynamical analysis of the interfacial hydrogen migration mediated by scanning tunneling microscopy (STM). Contributions from the STM-current and from the non-adiabatic couplings are taken into account using only first principle models. The slight asymmetry of the tunnelling rates with respect to the potential bias sign inferred from experimental observations is reproduced by weighting the contributions of the metal acceptor-donor states for the propagation of the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As a matter of fact, the DFT investigations presented here serve as a basis for a quantum dynamical study to be published elsewhere. 22 The paper is organised as follows: Sec. II deals with the calculations details.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the DFT investigations presented here serve as a basis for a quantum dynamical study to be published elsewhere. 22 The paper is organised as follows: Sec. II deals with the calculations details.…”
Section: Introductionmentioning
confidence: 99%
“…Illustratively, in the STM-induced manipulation of hydrogen on/in Pd(111), 22,23 the potential energy topography is decisive in the dynamics description, as it was shown that a quasi-thermal mechanism promoted by NAC suffices to explain the H-transfer behaviour under a wide range of external parameters, e.g., tunneling bias and current intensity. 24 In the present work we calculate, by means of densityfunctional theory (DFT), the potential energy landscape along a one-dimensional adiabatic reaction path to describe the trans ↔ cis tautomerisation of the isolated porphycene molecules adsorbed on Cu(111). That, in conjunction with the electronic structure analysis for both tautomers in their equilibrium configurations, serves the double purpose of (i) extracting information from the STM images (e.g., tautomer recognition, molecule buckling, and other geometrical parameters) and (ii) addressing the degree of importance of the van der Waals (vdW) interactions in the system.…”
Section: Introductionmentioning
confidence: 99%
“…The term in parentheses describes the probability of excitation of the locally harmonic mode Q α as the ratio of upward to downward rates. As demonstrated elsewhere, ,, these rates are a function of the STM parameters (bias voltage U and current intensity I ), the temperature, and the intermode coupling. Note that eq is the low-bias, low-temperature limit of a more general equation (see the SI), such that only the first excited state of each mode contributes to the potential deformation.…”
mentioning
confidence: 59%
“…The driving force for STM-induced reactions on metallic surfaces is the nonadiabatic coupling (NAC) between the excited electrons of the substrate and the adsorbate internal vibrations. Reactions involving large-amplitude motions require proper treatment of intermode couplings beyond the harmonic approximation. , A few theories have been proposed to account for anharmonic coupling in the NAC terms, either along the reaction path, by introducing coupling terms with specific soft modes, or by increasing dimensionality. Although promising, these methods remain only tractable in a low-dimensional space, where only a few relevant degrees of freedom are active.…”
mentioning
confidence: 99%
See 1 more Smart Citation